Algebraic constructions of rotated unimodular lattices and direct sum of Barnes-Wall lattices - Strapasson, João Eloir; Ferrari, Agnaldo José [UNESP]; Jorge, Grasiele Cristiane; Costa, Sueli Irene Rodrigues (World Scientific Publishing, 2020)
In this paper, we construct some families of rotated unimodular lattices and rotated direct sum of Barnes-Wall lattices BWn for n = 4, 8 and 16 via ideals of the ring of the integers azeta&2rq + ;zeta&2rq-1] for q = 3, 5 and 15. We also construct rotated BW16 and BW32-lattices via a;-submodules of azeta&2r15 + ;zeta&2r15-1]. Our focus is on totally real number fields since the associated lattices have full diversity and then may be suitable for signal transmission over both Gaussian and Rayleigh fading channels. The minimum product distances of such constructions are also presented here.
Keywords: Barnes-Wall lattices; cyclotomic fields; minimum product distance; Unimodular lattices